2020
DOI: 10.1080/2162402x.2020.1758004
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone premedication suppresses vaccine-induced immune responses against cancer

Abstract: Glucocorticosteroids (GCS) have an established role in oncology and are administered to cancer patients in routine clinical care and in drug development trials as co-medication. Given their strong immunesuppressive activity, GCS may interfere with immune-oncology drugs. We are developing a therapeutic cancer vaccine, which is based on a liposomal formulation of tumor-antigen encoding RNA (RNA-LPX) and induces a strong T-cell response both in mice as well as in humans. In this study, we investigated in vivo in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
0
15
0
1
Order By: Relevance
“…Data on the effect of steroids on mRNA vaccine-induced antigen-specific T cell response are limited. One study demonstrated that dexamethasone given before, but not after, an mRNA-based cancer vaccine resulted in reduced activation of antigen-specific T cells 6 . In the case under study, steroids were administered 10 d after vaccination and unlikely to have affected vaccine-specific immune response.…”
Section: Mainmentioning
confidence: 99%
“…Data on the effect of steroids on mRNA vaccine-induced antigen-specific T cell response are limited. One study demonstrated that dexamethasone given before, but not after, an mRNA-based cancer vaccine resulted in reduced activation of antigen-specific T cells 6 . In the case under study, steroids were administered 10 d after vaccination and unlikely to have affected vaccine-specific immune response.…”
Section: Mainmentioning
confidence: 99%
“…While this has led to significant differences in distribution, sensitivity and ligand specificity of PRRs, it has also resulted in differentiating evolutionary strategies for resistance and tolerance between humans and mice 33 . Relative to human response, mice have been found to be extremely resilient to different inflammatory stimuli 18,19,33 , including RNA-LPX vaccines 13,17 . In this study, we demonstrated that vaccine-induced systemic inflammatory responses are driven by IL-1 and antagonized by endogenous IL-1ra, and that these findings can be generalized to other forms of innate immune stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to humans, C57BL/6 and Balb/c mice are remarkably tolerant to RNA vaccines and only display limited systemic cytokine release following intravenous (IV) administration of liposomal, unmodified RNA (RNA-LPX) vaccine 13,17 . Even at doses of RNA (50µg) that are well-tolerated in mice, patients exhibit transient mild to moderate flulike symptoms that constrain dose exploration to a narrow range and possibly limit optimal T cell responses 6,8,9 .…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…As would be expected, these effects are not target cell specific and would also be apparent outside of anti-tumor immunity. Indeed, premedication of tumor-bearing mice with Dex inhibited vaccine-dependent induction of serum cytokines and chemokines and reduced both the number and the activation of conventional DCs expressing vaccine encoded antigens [52], suggesting that induction therapy with Dex alone might impair off-target immune responses. In fact, protocols involving Dex are a risk factor for infection in MM patients undergoing induction therapy [27].…”
Section: Dexamethasonementioning
confidence: 99%